BIOMECHANICAL EVALUATION OF POLYAXIAL ANGULAR STABLE PLATES IN THE MANAGEMENT OF TIBIAL PLATEAU FRACTURES - Norin Forna; Paul-Dan Sîrbu; Savin Liliana; Lucian Eva; Wilhelm Friedl; Eugen Carata; Tudor Pinteală; Răzvan Tudor; Mihnea Theodor Sîrbu (Romanian Journal of Oral Rehabilitation)
Biomechanical efficacy is critical in managing tibial plateau fractures. This study compared the performance of polyaxial screw-plate implant systems under axial loading conditions using synthetic bone models. Osteosynthesis methods involving lateral, medial, and combined (lateral + medial) plates were evaluated. Although no statistically significant differences in stiffness and stability were observed across all groups under progressive axial loading, the combined lateral and medial plate technique demonstrated superior biomechanical performance compared to individual plate use. Notably, the lateral plate method outperformed the medial plate approach but was surpassed by the dual plate configuration. A statistically significant, directly proportional relationship between time intervals and displacement, along with an inverse correlation between time intervals and stiffness, was observed across all test groups. These findings highlight that combining lateral and medial plates enhances rigidity and stability, particularly under axial loading, making it a preferred approach for treating tibial plateau fractures.